Extended absorption window and improved stability of cesium-based triple-cation perovskite solar cells passivated with perfluorinated organics - Salim, K. M. Muhammed (2020)
Despite the high-quality films achieved with triplecation perovskites, the deviation from an optimized band gap by virtue of Shockley-Queisser estimation signifies consequential light absorption losses in this system. Herein, it is shown that, by passivating the perovskite surface with a hydrophobic fluorinated organic salt, namely, pentafluoropropylamonium iodide (PFPAI), not only is the band gap narrowed but the process also contributes toward the modulation of surface and electronic properties of the resulting film. The cumulative effect of these factors promotes the enhancement in the power conversion efficiency (PCE) and moisture stability of the perovskite solar cells (PSCs) fabricated with the PFPAI-passivated films. Suppression of surface defects and mitigation of interfacial charge recombination in the treated film are in good agreement with the longer photoluminescence (PL) decay lifetime observed. The PFPAI-passivated PSC afforded a PCE of 16.6% with good ambient stability, evidenced by minimal change in the normalized PCE on storage in a relative humidity (RH) environment of 55% over a period exceeding 169 days.